2005
DOI: 10.1302/0301-620x.87b7.16240
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients before and after surgery for a herniated lumbar disc

Abstract: We investigated the pre-operative and one-year post-operative health-related quality of life (HRQOL) outcome by using a Euroqol (EQ-5D) questionnaire in 263 patients who had undergone surgery for herniation of a lumbar disc. Data from the National Swedish Register for lumbar spinal surgery between 2001 and 2002 were used and, in addition, a comparison between our cohort and a Swedish EQ-5D population survey was performed. We analysed the pre- and post-operative quality of life data, age, gender, smoking habits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 16 publications
5
70
2
4
Order By: Relevance
“…Akmal et al [2] also demonstrated the toxicity of nicotine on bovine in vitro intervertebral disc cells. We found that nonsmokers had better outcomes than smokers, which is consistent with previous studies [6,17,24]. Nonetheless, we found that smokers and nonsmokers had no difference in the surgical treatment effect.…”
Section: Discussionsupporting
confidence: 92%
“…Akmal et al [2] also demonstrated the toxicity of nicotine on bovine in vitro intervertebral disc cells. We found that nonsmokers had better outcomes than smokers, which is consistent with previous studies [6,17,24]. Nonetheless, we found that smokers and nonsmokers had no difference in the surgical treatment effect.…”
Section: Discussionsupporting
confidence: 92%
“…This was so in terms of both the global outcome (a retrospective rating of the patient's perceived success of the procedure), the prospectively measured changes in the multidimensional patient-orientated COMI LP and LP-LBP were not selected for inclusion in the final forward conditional step, once LBP had been selected as the most significant predictor score and the reduction in leg pain. This finding correlates well with our clinical experience and may appear intuitive; however, it has been formally investigated in very few studies to date [6,20]. In a recent systematic review of prospective studies examining predictors of outcome of discectomy, a high preoperative pain level was identified as carrying ''positive evidence'' for being one of many bio-psychosocial risk factors for a poor outcome [5].…”
Section: Discussionsupporting
confidence: 70%
“…However, the amount of concomitant preoperative low back pain has rarely been examined as a risk factor. Some studies have ascertained that the presence of LBP [20] and a long history of LBP [6] preoperatively are associated with a poorer outcome and/or lower quality of life, but none have actually quantified the relative levels of LBP and LP prior to surgery. To advise our patients and set reasonable expectations in such circumstances, we need to better understand the relationship between preoperative low back pain and the outcome of surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The EQ-5D has also been used to evaluate patients who have undergone spine surgery. Jansson et al studied health-related QOL in patients before and after surgery for herniated lumbar disc and lumbar spinal stenosis; they report that the post-surgery EQ-5D utility weight improved from 0.29 (preoperatively) to 0.70 in herniated lumbar disc and from 0.36 to 0.64 in lumbar spinal stenosis [24,25]. However, to our knowledge, no study has evaluated health-related QOL using the EQ-5D before and after surgical reconstruction for cervical disorders in RA.…”
Section: Discussionmentioning
confidence: 99%